Consumption and real exchange rates in professional forecasts - Michael B. Devereux; Gregor W. Smith; James Yetman (Queen's University, Department of Economics, 2009)
Standard models of international risk sharing with complete asset markets predict a positive association between relative consumption growth and real exchange-rate depreciations across countries. The striking lack of evidence for this link - the consumption/real exchange-rate anomaly or Backus-Smith puzzle - has prompted research on risk-sharing indicators with incomplete asset markets. That research generally implies that the association holds in forecasts, rather than realizations. Using professional forecasts for 28 countries for 1990-2008 we find no such association, thus deepening the puzzle. Independent evidence on the weak link between forecasts for consumption and real interest rates suggests that the presence of 'hand-to-mouth' consumers may help to explain the evidence.
Keywords: F37; F41; F47; 330; International risk-sharing; Backus-Smith puzzle; Konsum; Kaufkraftparität; Abwertung; Risikopräferenz; Welt